2015
DOI: 10.1161/circresaha.116.305060
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Fine Particulate Air Pollution, Cardiometabolic Disorders, and Cardiovascular Mortality

Abstract: Rationale: Growing evidence suggests that long-term exposure to fine particulate matter (PM 2.5 ) air pollution contributes to risk of cardiovascular disease (CVD) morbidity and mortality. There is uncertainty about who are most susceptible. Individuals with underlying cardiometabolic disorders, including hypertension, diabetes mellitus, and obesity, may be at greater risk. PM 2.5 pollution may also contribute to ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
195
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 333 publications
(218 citation statements)
references
References 36 publications
4
195
1
8
Order By: Relevance
“…Odds ratios using both the standard linear and threshold models were estimated for all ACS, STEMI, NSTEMI, UA, and NSTE‐ACS events for all patients and for patients with and without CAD. For comparison purposes, and consistent with reporting from various studies and reviews of the literature,1, 2, 3, 4, 5, 6, 7, 8, 11, 14, 15, 16 odds ratios associated with 10‐μg/m 3 incremental increases in PM 2.5 concentration are presented.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Odds ratios using both the standard linear and threshold models were estimated for all ACS, STEMI, NSTEMI, UA, and NSTE‐ACS events for all patients and for patients with and without CAD. For comparison purposes, and consistent with reporting from various studies and reviews of the literature,1, 2, 3, 4, 5, 6, 7, 8, 11, 14, 15, 16 odds ratios associated with 10‐μg/m 3 incremental increases in PM 2.5 concentration are presented.…”
Section: Methodsmentioning
confidence: 93%
“…Various prospective cohort studies of long‐term exposure (years or decades) have found that elevated PM 2.5 exposures are associated with increased risk of cardiovascular disease mortality3, 4, 5, 6, 7, 8, 9 and may contribute to the initiation and progression of related chronic diseases including atherosclerosis, hypertension, and diabetes 10, 11. The Global Burden of Disease 2010 analysis reported comparative burden of disease risk assessments from 67 risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, fine particulate matter (PM2.5) was used to measure levels of air pollution concentrations as it is a common air pollutant used in related studies (Anderson et al, 2012;Pope et al, 2015;Chen et al, 2012;Li et al, 2016b). Although annual mean PM2.5 estimates in 2015 are available in the Air Quality in Scotland (Ricardo Energy & Environment, 2016), the spatial resolution of the PM2.5 concentration data is 1 km × 1 km.…”
Section: Air Pollution Datamentioning
confidence: 99%
“…As the impact of air pollution exposure on health is not as noticeable as that of traffic accidents, people are likely to ignore the harmful effect of air pollution exposure. In fact, air pollution exposure tends to have both a short-term and long-term effects on human health (WHO 2016;Anderson et al, 2012;Lipsett et al, 2011;Pope et al, 2015;Chen et al, 2012;Li et al, 2016;Shah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Research has linked poor air quality with numerous adverse health outcomes, including but not limited to, cardiovascular disease [1][2][3], myocardial infarction and cerebrovascular disease [4,5], respiratory conditions requiring hospital admission [6,7] and lung cancer [8,9]. Poor air quality and adverse health outcomes are not geographically isolated events, with major studies carried out in North America [10,11], South America [12], Europe [13], Eastern Asia [14] and India [15], all reporting positive associations.…”
Section: Introductionmentioning
confidence: 99%